Раскладываем на множители sin+sin3x+sin5x sinx+sin3x+sin5x=sinx+sin(x+2x)+sin(3x+2x)=sinx+sinx*cos2x+cosx*sin2x+sin3x*cos2x+cos3x*sin2x=sinx+sinx*cos2x+2sinx*cos^2x+sin(2x+x)*cos2x+cos(x+2x)*sin2x=sinx+sinx*cos2x+2sinx*cos^2x+(2sinx*cos^2x+cos2x*sinx)*cos2x+(cosx*cos2x-sinx*sin2x)*2sinx*cosx=sinx(1+cos2x+2cos^2x+(2cos^2x+cos2x)*cos2x+2cosx*(cosx*cos2x-sinx*sin2x))=sinx(1+cos2x+2cos^2x+cos^2(2x)+2cos^2x*cos2x+2cos^2x*cos2x-4sin^2x*cos^2x)=sinx(1+cos2x+2cos^2x+cos^2(2x)+4cos^2x*cos2x-sin^2(2x))=sinx(2cos^2(2x)+cos2x+2cos^2x+4cos^2x*cos2x)=sinx(2cos^2(2x)+cos2x+1+cos2x+4cos^2x*cos2x)=sinx(2cos^2(2x)+2cos(2x)+2(1+cos2x)*cos2x+1)=sinx(2cos^2(2x)+2cos2x+2cos2x+2cos^2(2x)+1)=sinx(4cos^2(2x)+4cos(2x)+1)=sinx*(2cos(2x)+1)^2
Раскладываем на множители sin+sin3x+sin5x sinx+sin3x+sin5x=sinx+sin(x+2x)+sin(3x+2x)=sinx+sinx*cos2x+cosx*sin2x+sin3x*cos2x+cos3x*sin2x=sinx+sinx*cos2x+2sinx*cos^2x+sin(2x+x)*cos2x+cos(x+2x)*sin2x=sinx+sinx*cos2x+2sinx*cos^2x+(2sinx*cos^2x+cos2x*sinx)*cos2x+(cosx*cos2x-sinx*sin2x)*2sinx*cosx=sinx(1+cos2x+2cos^2x+(2cos^2x+cos2x)*cos2x+2cosx*(cosx*cos2x-sinx*sin2x))=sinx(1+cos2x+2cos^2x+cos^2(2x)+2cos^2x*cos2x+2cos^2x*cos2x-4sin^2x*cos^2x)=sinx(1+cos2x+2cos^2x+cos^2(2x)+4cos^2x*cos2x-sin^2(2x))=sinx(2cos^2(2x)+cos2x+2cos^2x+4cos^2x*cos2x)=sinx(2cos^2(2x)+cos2x+1+cos2x+4cos^2x*cos2x)=sinx(2cos^2(2x)+2cos(2x)+2(1+cos2x)*cos2x+1)=sinx(2cos^2(2x)+2cos2x+2cos2x+2cos^2(2x)+1)=sinx(4cos^2(2x)+4cos(2x)+1)=sinx*(2cos(2x)+1)^2
теперь раскладываем cosx+cos3x+cos5x cosx+cos3x+cos5x=cosx+cos(2x+x)+cos(2x+3x)=cosx+cos2x*cosx-sin2x*sinx+cos2x*cos3x-sin2x*sin3x=cosx+cos2x*cosx-2sin^2x*cosx+cos2x*cos(x+2x)-2sinx*cosx*sin(x+2x)=cosx+cos2x*cosx-2sin^2x*cosx+cos2x*(cosx*cos2x-2sin^2x*cosx)-2sinx*cosx*sin(x+2x)=cosx(1+cos2x-2sin^2x+cos^2(2x)-2sin^2x*cos2x-2sinx*(sinx*cos2x+cosx*sin2x))=cosx(2cos2x+cos^2(2x)-2sin^2x*cos2x-2sin^2x*cos2x-4sin^2x*cos^2x)=cosx(2cos2x+cos^2(2x)-4sin^2x*cos2x-4sin^2x*cos^2x)=cosx(2cos2x+cos^2(2x)-2(1-cos2x)*cos2x-sin^2(2x))=cosx(2cos2x+cos^2(2x)-sin^2(2x)-2cos2x+2cos^2(2x))=cosx(2cos^2(2x)-1+2cos2x-2cos2x+2cos^2(2x))=cosx(4cos^2(2x)-1)=cosx(2cos2x-1)(2cos2x+1) подставляем в уравнение:
= log (1/3)6^2 - log(1/3)√(400) + log(1/3)(∛45)^3 =
= log(1/3) 36 - log (1/3) 20 + log(1/3) 45 =
= log (1/3) (36/20) + log (1/3) 45 =
= log (1/3) (9/5) + log (1/3) 45 =
= log (1/3) ((9*45)/5) =
= log (1/3) 81 =
= log 3^(-1) 3^4 =
= - log 3 3^4 = - 4